'Focus on the bigger picture:' an anti-deficit achievement examination of black male scholar athletes in science and engineering at a historically white university (HWU). Issue 2 (2nd July 2016) - Cooper, Joseph N.
Abstract: The purpose of this study was to examine the experiences of black male scholar athletes in science and engineering majors at a Division I research-intensive historically white university (HWU) and identify key influences that facilitated their academic achievement. Participants included three black male scholar athletes in science and/or engineering majors at a Division I research-intensive HWU. A single focus group, three in-depth individual interviews and an eight-item demographic questionnaire were employed to investigate the phenomenon of interest. The prove them wrong syndrome and an anti-deficit achievement framework were incorporated to explore the pre-college and college influences that contributed to the participants' educational outcomes. Emergent themes highlighted the pivotal role of strong familial support, academic self-efficacy, strategic responsiveness to negative stereotypes and select benefits from athletic participation resulted in the participants' academic achievement. Implications for policy and practice are discussed .